The effect of chronic khat consumption on sperm count and motility in parent mice and their offspring - AlBadri, Cinaria Tarik; Al-Ani, Imad Matloub Dally; Hiba, Hassan Mohamed (EuroJournals Publishing, Inc., 2012)
Khat is considered a psychoactive drug and has many side effects on different parts of the body organs. In this study the effects of khat on sperm count and motility in parent mice and their offspring were investigated. Animals were divided into two groups, Group 1 (khat group) contained twelve male and twelve female mice, and they were given a daily dose of (50mg/kg) body weight khat extract by gastric gavage for four and eight weeks. Group 2 (control group) also contained twelve male and twelve female mice and received normal access of food and water. After four weeks of treatment, the males and females were allowed to mate and khat treatment continued for up to another four weeks. Twenty four male offspring from group 1 and group 2 were selected randomly and allowed to become mature. Male parent mice were killed at the 4th and 8th weeks of treatment, and their male offspring were killed when they reached maturity age (6-8weeks). Physiological examination of the sperm solution showed that there was a significant increase in sperm count and motility after 4 and 8 weeks of khat treatment, and in their adult offspring. Furthermore, histological changes were found in testicular sections of the adult male mice.